Improved Power Effective Node Combined Heterogeneous Path Protocol for Enhance Network Lifetime Based on Cloud Resource Management in WSN - Natarajan, Vignesh Prasanna; Shekhar, S. N. Chandra; Kumar, R. Krishna; Swaminathan, A.; Harika, D.; Mahalakshmi, G. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Nowadays, sensor nodes are connected wirelessly to the Wireless Sensor Network (WSN). A WSN contains frequent sensor nodes spread throughout surroundings. These nodes are responsible for identifying, approximating, and receiving information. There is a unique technology called a "sensor cloud" that combines the sensor capabilities of WSNs with the architecture of Cloud Computing (CC). The small sensor nodes can sense, process, and transmit data. However, it is difficult and expensive to extend the lifespan of WSNs. Using energy-efficient routing protocols ensures reliable data transmission and prolongs the network's lifespan. However, control limitations can have a substantial control on the overall lifetime of the network. Since batteries power nodes in WSNs, they will eventually lose all power after a certain period. Therefore, we introduced the Improved Power Effective Node Combined Heterogeneous Path (IPENCHP) protocol to solve the above problem. Initially, we use the Enhanced Butterfly Optimal Cluster Algorithm (EBOCA) to select an ideal Cluster Head (CH) from a group of nodes. Furthermore, the ONND method can enhance the network's energy efficiency of the node. The path between CHs and BSs is found using the Ant Colony Optimum Based Path Distance (ACOPD) algorithm. Finally, the IPENCHP protocol can prolong the network lifetime of cloud resource management by assessing the energy communication level within a cluster. According to the simulation results, IPENCHP outperforms regarding energy efficiency, packet loss rate, energy consumption, performance latency, and Throughput.